2018
DOI: 10.1177/0146167218760799
|View full text |Cite
|
Sign up to set email alerts
|

You Can’t See the Real Me: Attachment Avoidance, Self-Verification, and Self-Concept Clarity

Abstract: Attachment shapes people's experiences in their close relationships and their self-views. Although attachment avoidance and anxiety both undermine relationships, past research has primarily emphasized detrimental effects of anxiety on the self-concept. However, as partners can help people maintain stable self-views, avoidant individuals' negative views of others might place them at risk for self-concept confusion. We hypothesized that avoidance would predict lower self-concept clarity and that less self-verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
4
27
0
3
Order By: Relevance
“…Both of these results align with previous findings (Shallcross et al, 2011), showing that insecure attachment may manifest in lower perceived responsiveness in the daily couple life. For avoidant attachment, we additionally found that a higher level of avoidant attachment was linked to a lower average level of self‐disclosure, which is also in line with previous research (Bradford et al, 2002; Emery et al, 2018): Considering that self‐disclosure relates to intimacy (Laurenceau, Barrett, & Pietromonaco, 1998) and that people high in avoidant attachment tend to feel uncomfortable with intimacy (Mikulincer & Shaver, 2007), it is unsurprising that self‐disclosure reflects an uncomfortable undertaking for people high in avoidant attachment (Keelan et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both of these results align with previous findings (Shallcross et al, 2011), showing that insecure attachment may manifest in lower perceived responsiveness in the daily couple life. For avoidant attachment, we additionally found that a higher level of avoidant attachment was linked to a lower average level of self‐disclosure, which is also in line with previous research (Bradford et al, 2002; Emery et al, 2018): Considering that self‐disclosure relates to intimacy (Laurenceau, Barrett, & Pietromonaco, 1998) and that people high in avoidant attachment tend to feel uncomfortable with intimacy (Mikulincer & Shaver, 2007), it is unsurprising that self‐disclosure reflects an uncomfortable undertaking for people high in avoidant attachment (Keelan et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…As for cognitive relationship components, individuals with avoidant attachment suppress unwanted distress‐related thoughts to preserve their independence and to avoid contemplating abandonment (Shallcross et al, 2011). Regarding behavioural relationship components, individuals with avoidant attachment prefer independence to dependence and are reluctant to seek emotional intimacy, because they find such intimacy uncomfortable (Collins & Read, 1990; Hazan & Shaver, 1987; Simpson & Rholes, 2012); they are less likely to self‐disclose to and trust their partner (Emery, Gardner, Carswell, & Finkel, 2018); and when they self‐disclose to their partner, they feel uncomfortable (e.g. Bradford, Feeney, & Campbell, 2002; Keelan et al, 1998).…”
Section: Personality–relationship Transactionsmentioning
confidence: 99%
“…Both of these results align with previous findings (Shallcross et al, 2011), showing that insecure attachment may manifest in lower perceived responsiveness in the daily couple life. For avoidant attachment, we additionally found that a higher level of avoidant attachment was linked to a lower average level of self-disclosure, which is also in line with previous research (Bradford et al, 2002;Emery et al, 2018): Considering that self-disclosure relates to intimacy (Laurenceau, Barrett, & Pietromonaco, 1998) and that people high in avoidant attachment tend to feel uncomfortable with intimacy (Mikulincer & Shaver, 2007), it is unsurprising that self-disclosure reflects an uncomfortable undertaking for people high in avoidant attachment (Keelan et al, 1998).…”
Section: Mediationsupporting
confidence: 90%
“…As for cognitive relationship components, individuals with avoidant attachment suppress unwanted distress-related thoughts to preserve their independence and to avoid contemplating abandonment (Shallcross et al, 2011). Regarding behavioural relationship components, individuals with avoidant attachment prefer independence to dependence and are reluctant to seek emotional intimacy, because they find such intimacy uncomfortable (Collins & Read, 1990;Hazan & Shaver, 1987;Simpson & Rholes, 2012); they are less likely to self-disclose to and trust their partner (Emery, Gardner, Carswell, & Finkel, 2018); and when they self-disclose to their partner, they feel uncomfortable (e.g. Bradford, Feeney, & Campbell, 2002;Keelan et al, 1998).…”
Section: Insecure Attachmentmentioning
confidence: 99%
“…In addition to exploring novel contexts and consequences of motives to share reality, the present research also contributes to our understanding of how the self is impacted by interpersonal relationships. Previous research has demonstrated that dyadic relationships can impact the content of the self-concept (Aron, Aron, Tudor, & Nelson, 1991), evaluations of the self (Baldwin, Carrell, & Lopez, 1990), and selfconcept clarity (Emery et al, 2018;Luchies, Finkel, McNulty, & Kumashiro, 2010;Slotter, Gardner, & Finkel, 2010). However, relatively little research has explored how social networks influence the self-concept (cf.…”
Section: Discussionmentioning
confidence: 99%